The impact of COVID-19 on Ugandan firms - Alfonsi, Livia; Bassi, Vittorio; Manwaring, Priya; Ngategize, Peter; Oryema, John; Stryjan, Miri; Vitali, Anna (International Growth Center (IGC) Uganda, 2021)
The COVID-19 pandemic came at an enormous cost to both developed and developing countries, and Uganda is no exception to this. Though the country has so far been shielded from the worst in terms of health impact, measures put to curb the spread of COVID-19 and the sharp global downturn in economic activity have hit the economy hard. For instance, severe limitations on international transport have reduced exports and tourism and restricted access to key industrial inputs. At the same time, the collapse in the world economy has reduced aggregate demand and lowered remittances from Ugandans living abroad. Lockdown measures between March and May 2020 compounded economic difficulties by preventing people from working and limiting internal mobility. As a result of the global crisis, GDP growth slowed from 6.8% in FY 2018/19 to 2.9% in FY 2019/20, and is expected to grow at a similar level in FY 2020/21 (World Bank, 2020).